The effect of public pension wealth on saving and expenditure - Marta Lachowska; Michał Myck (W.E. Upjohn Institute for Employment Research, 2015)
In order to study whether public pension systems displace private saving, we use the quasiexperimental variation in pension wealth created by Poland's 1999 pension reform. Using the 1997-2003 Polish Household Budget Surveys, we begin by estimating "difference-indifferences" regressions, where we compare household saving and expenditure across time and between cohorts affected and unaffected by the reform. Next, we estimate the extent of crowdout by using two-stage least squares. We identify the effect of pension wealth on private saving by using the cohort-by-time variation in pension wealth that is explained by the reform. We find that one additional Polish zloty, or PLN, of pension wealth crowds out about 0.24 PLN in household saving. We also find heterogeneity in responses. For the middle-aged cohorts, we find a large public pension crowd-out of private saving (about 0.54 PLN of private saving for each 1 PLN of public pension wealth), while the crowd-out for younger cohorts equals about 0.30 PLN of private saving per 1 PLN. Finally, we find a close-to-complete crowd-out among highly educated households.
Keywords: E21; H55; I38; P35; 330; pension reforms; crowd-out effect; retirement saving; difference-in-differences; natural experiment